Bonne nature, mauvais artifice ? L’Église catholique et l’écologie : retour sur Laudato Si’ - Jean-Michel Le Bot (Éditions en environnement VertigO, 2017)
In the spring of 2015, the encyclical letter of the pope Francis, Laudato Si’, adressed the subject of ecology and the protection of environment and opposed the idea, asserted nearly fifty years ago by Lynn T. White, that the ecological crisis was largely due to christian anthropocentrism. Our paper replace the encyclical in the long-term history of the catholic doctrine. It observes that suspicion toward artificial methods and preference given to natural methods has become during the 20th century one of the main distinctions in the Catholic Church’s position regarding birth control. This was something new if compared to the doctrine inherited from saint Augustine. But it was already a step toward the ecological position, expressed, for instance, by the pioneers of organic agriculture around the middle of the century. All that remained was to widen the scope, from natural methods of birth control to human ecology and from human ecology to integral ecology.